Association of PTPN22 SNP1858 (rs2476601) and Gene SNP1123 (rs2488457) Polymorphism With Primary Immune Thrombocytopenia Susceptibility: A Meta-Analysis of Case-Control Studies and Trial Sequential Analysis - Tian, Haokun; Xu, Weikai; Wen, Lequan; Tang, Lirui; Zhang, Xinyuan; Song, Tiangang; Yang, Changsen; Huang, Peng (Frontiers in Genetics, 2022)
Objective: Systematic review of the association of protein tyrosine phosphatase non-receptor Type 22 (PTPN22) gene 1858 and 1123 sites single nucleotide polymorphism (SNP) with the susceptibility of primary immune thrombocytopenia (ITP). Method: Database searched includes Pubmed, Embase, Web of Science, CNKI, CBM, VIP and WanFang Data. The retrieval period is from the establishment of the database to June 30, 2021. After screening articles according to inclusion and exclusion criteria, the data were extracted and methodological quality of the included studies was evaluated. Meta-analysis was performed using RevMan 5.4 and Stata 16.0 software. The combined OR value and its 95%CI were calculated. Sensitivity analysis and publication bias assessment were performed. Trial sequential analysis (TSA) was performed using TSA 0.9.5.10 Beta software. Results: A total of 10 studies with 10 articles were included, with a total of 932 cases and 2112 controls. The results of meta-analysis showed that for SNP1858, the susceptibility of TT genotype to ITP was 5.01 times higher than CC genotype [95%CI (1.81, 13.86), P=0.002]. For SNP1123, G allele carriers were more susceptible to ITP than C allele carriers [OR=1.23, 95%CI (1.05, 1.45), P=0.01], and GG genotype carriers were 1.51 times more susceptible to ITP than CC genotype carriers [95%CI (1.11, 2.06), P=0.009]. Although the results are statistically significant, the results of sensitivity analysis showed certain limitations of stability, and the TSA analysis still indicated the possibility of false positive. No significant publication bias was observed. Conclusion: PTPN22 gene SNP1858 (rs2476601) and SNP1123 (rs2488457) polymorphisms are associated with susceptibility to primary immune thrombocytopenia. Due to the limitation of the number and quality of the included studies, the above conclusions need to be verified by more high-quality studies.